A clinical, radiological and in vitro strain investigations of mandibular implant overdentures / Tameem Khuder Jassim - Tameem Khuder, Jassim (2018)
Conventional complete denture (CD) and two mandibular implant-overdenture (IOD) prostheses with non-balanced occlusal scheme can induce residual ridge resorption (RRR) and increase the risk of denture fracture. Nevertheless, the association between occlusal force distribution to other clinical and mechanical factors are not that clear. Objectives: To compare masticatory performance, occlusal force distribution, and patient-reported outcomes in patients wearing IOD and CD, and to investigate the effect of two mandibular implants and clinical parameters on maxillary and mandibular residual ridge resorption (RRR). Finite element analysis (FEA) was applied to investigate the in vitro strain distribution using loading simulation according to the clinically determined occlusal force distribution. The fracture risk was predicted based on tensile strain distribution at the implant attachment interface of IOD prostheses and compared with the frequency of clinical complications recorded for two attachment types, from the follow-up records of patients with IOD prostheses. Methods: Twenty-three patients in each of the IOD (age 66 ± 8 years) and CD (age 65 ± 10 years) groups were recalled 3-4 years after provision of the prostheses. Masticatory performance was determined based on the patients’ ability to chew two-colored wax cubes and mixing ability index (MAI) derived. The percentages of occlusal force (OF%) distribution at anterior and posterior quadrants of the arch were recorded using a digital occlusal analyzer (T-scan III). The radiographic images of the dental panoramic radiograph were compared with the baseline for RRR determination using the bone area index measurement method. Patient-reported outcomes were analyzed using the shortened Malaysian version of Oral Health-related Quality of Life (OHIP-14) and denture satisfaction (DS) questionnaires. For FEA, maxillary and mandibular models were constructed from cone-beam computed tomographic data of a patient. The anterior and posterior vertical loads were simulated according to the OF% distribution obtained from the respective patient groups. Compressive and tensile strains were compared with the frequency of clinical complications recorded in IOD patients between the two implant attachment types. Results were statistically analyzed with a 95% confidence interval. Results: The mean MAI of the CD and IOD groups showed no significant difference (P=0.134), while significant difference was observed in the mean OF% (P=0.002). For patient-reported outcomes, the total scores of OHIP-14 (P=0.027) and DS (P=0.030) between groups showed significant differences. The IOD showed significantly less bone resorption compared to the CD groups in the maxillary anterior area (P=0.013). Multivariate regression analyses showed significant association between RRR and OF% at the anterior maxilla (P=0.000) and posterior mandible (P=0.023). The frequency of mechanical complications clinically observed with telescopic were significantly greater than with Locator attachments (P=0.005). The FEA results showed greater strain concentration on the denture impression surface at the attachment-acrylic interface of both telescopic- (561με) and Locator- retained (323με) IODs. Conclusions: Patients with mandibular IODs showed better OHIP-14 and DS, but with no significant difference in the masticatory performance compared to CD patients. Residual ridge resorption was significantly associated with the occlusal force distribution and the type of prostheses. A higher tensile strain produced by telescopic attachment compared to Locator attachment interface supported the clinical observation of greater complication with telescopic IODs.